Paradoxes of domestication: approximations to the problematic relationship between freedom and eugenics - Cornejo Puschner, Sascha Miguel (2020)
During the last decade, technological development has brought the need of setting precise boundaries regarded to organic bodies. Diverse perspectives coming from Social Sciences and Political Philosophy have problematized/questioned this latter, which has been loosely regulated by legal norms, in relation to the appropriation of molecular and genetic components. However, a broad debate about the dangers of Biotechnology and its transformational power has arisen. The practice of this science and the new ethical and axiological requirements demanded to frame the intervention of technology, in organic human processes. This article aims at contributing with a number of critical perspectives to this theoretical debate.